2022
DOI: 10.3389/fphys.2022.856427
|View full text |Cite
|
Sign up to set email alerts
|

Expression Regulation of Water Reabsorption Genes and Transcription Factors in the Kidneys of Lepus yarkandensis

Abstract: Lepus yarkandensis is a desert-dwelling animal that has various adaptations to cope with drought. The kidney maintains water and acid-base balance mainly through the vasopressin-regulated water reabsorption pathway and proximal tubular bicarbonate reabsorption pathway. In this study, we compared the differentially expressed genes (DEGs) and transcription factors in the kidneys of L. yarkandensis and Oryctolagus cuniculus to explore the relationship between the DEGs in kidneys and the animals’ adaptations. Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…These pathways and individual genes should be further investigated to define their functional relevance to osmoregulation. Furthermore, genes with reactive expression changes can be compared to those shown to be expressed differently between mesic and xeric species 45 , 46 to elucidate sources of desert adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…These pathways and individual genes should be further investigated to define their functional relevance to osmoregulation. Furthermore, genes with reactive expression changes can be compared to those shown to be expressed differently between mesic and xeric species 45 , 46 to elucidate sources of desert adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…KEGG analysis showed that the water reabsorption pathway was the first pathway involved by hypomethylated genes, which might be due to the selection of kidney cell lines. The kidney mainly maintained water and acid-base balance through vasopressin-regulated water reabsorption pathway and proximal tubular reabsorption pathway (Luo et al, 2022). PRV infection broke this balance relationship and the m 6 A modification level of related genes decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we examined pathways and their abundance variations through all trimesters. The proximal tubule bicarbonate reclamation pathway regulates the acid-base balance [52], and any disruptions in this pathway can lead to renal tubular acidosis (RTA) Although rare in pregnancy, RTA is associated with adverse pregnancy outcomes [53][54][55][56][57]. Similarly, systemic lupus erythematosus SLE is known to be associated with adverse pregnancy outcomes including PTB since women with SLE are more likely to experience complications such as fetal loss, PTB, and hypertensive disease [58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%